eHealth interventions for psychiatry in Switzerland and Russia: a comparative study - Olga Chivilgina; Bernice S. Elger; Bernice S. Elger; Ilya Fedotov; Fabrice Jotterand; Fabrice Jotterand (Frontiers Media S.A., 2024)
IntroductionDuring the past decade, the use of digital technology to promote mental health has increased dramatically. Additionally, the consequences of the COVID-19 pandemic, such as travel restrictions and the disruption of face-to-face interactions, have led to an increase in the use of digital technologies. A wide variety of technologies have been developed, including messaging chatbots, virtual reality technologies, direct-to-consumer apps, and even technologies that are fully integrated into clinical care tools.MethodsThe following qualitative study is based on the opinions of mental health specialists in both countries regarding the use of digital health technologies in psychiatry in Switzerland and Russia in 2019-2020. We investigate the state of adoption of digital technologies in the field of mental health, the meaning of such technologies, and the crucial factors in the use of such technologies in psychiatry.ResultsHealth care professionals in both Russia and Switzerland are well aware of these technologies. However, the use of digital technology to promote mental health has taken different paths in these two health care settings.